PREVALENCE OF DEPRESSIVE SYMPTOMS AMONG CHILDREN AND ADOLESCENTS WITH RHEUMATIC DISEASES - Julia Szklarska-Komenda; Maciej Komenda; Katarzyna Garncarz; Krzysztof Jamroch; Aleksandra Marek; Karolina Dziki; Wiktoria Dybizbańska; Zofia Nowakowska; Agnieszka Burzej; Mateusz Kacalak (International Journal of Innovative Technologies in Social Science, 2026)
Background. Although rheumatic disorders are commonly associated with adulthood, a considerable number of cases occur in children and adolescents. Paediatric rheumatic diseases such as juvenile idiopathic arthritis (JIA), childhood-onset systemic lupus erythematosus (cSLE) and juvenile fibromyalgia (JFM) are chronic conditions that significantly affect everyday activities and quality of life.Aim. This review aims to condense existing evidence regarding the prevalence of depressive symptoms among affected children and adolescents while emphasizing methodological challenges that shape reported outcomes.Material and methods. The literature search was conducted in PubMed (2013–2025) using terms related to depression, JIA, cSLE, JFM, rheumatology and paediatrics. Studies including children and adolescents were analysed, while adult-only papers were excluded.Results. Beyond physical symptoms JIA, cSLE, and JFM increase vulnerability to depressive symptoms. It is an under-recognised burden among paediatric patients. Despite this, the available research remains scarce, outdated, and methodologically inconsistent.Conclusion. Across the studies, depressive symptoms were consistently more common in paediatric rheumatologic patients than in healthy peers. However, prevalence varied widely depending on the assessment method. Self-report questionnaires detected far higher rates than clinical diagnoses.  Early psychiatric screening and appropriate psychological support are crucial, as the visibility of rheumatic symptoms (e.g., joint deformities, rashes, mobility impairments) and the resulting difficulties with social integration may further exacerbate emotional distress. Improving understanding of these associations will contribute to better clinical care and enhanced quality of life for this vulnerable patient population.